Incidence and survival in non-hereditary amyloidosis in Sweden - Hemminki Kari; Li Xinjun; Försti Asta; Sundquist Jan; Sundquist Kristina (BMC, 2012)
Abstract Background Amyloidosis is a heterogeneous disease caused by deposition of amyloid fibrils in organs and thereby interfering with physiological functions. Hardly any incidence data are available and most survival data are limited to specialist clinics. Methods Amyloidosis patients were identified from the Swedish Hospital Discharge and Outpatients Registers from years 2001 through 2008. Results The incidence of non-hereditary amyloidosis in 949 patients was 8.29 per million person-years and the diagnostic age with the highest incidence was over 65 years. Secondary systemic amyloidosis showed an incidence of 1 per million and a female excess and the largest number of subsequent rheumatoid arthritis deaths; the median survival was 4 years. However, as rheumatoid arthritis deaths also occurred in other diagnostic subtypes, the incidence of secondary systemic amyloidosis was likely to be about 2.0 per million. The median survival of patients with organ-limited amyloidosis was 6 years. Most myeloma deaths occurred in patients diagnosed with unspecified or 'other' amyloidosis. These subtypes probably accounted for most of immunoglobulin light chain (AL) amyloidosis cases; the median survival time was 3 years. Conclusions The present diagnostic categorization cannot single out AL amyloidosis in the Swedish discharge data but, by extrapolation from myeloma cases, an incidence of 3.2 per million could be ascribed to AL amyloidosis. Similarly, based on rheumatoid arthritis death rates, an incidence of 2.0 could be ascribed to secondary systemic amyloidosis.